Supraciliary versus intrascleral implantation with hema implant (Esnoper V‐2000) in deep sclerectomy: a multicenter randomized controlled trial. Issue 7 (31st May 2018) - Belda, Jose I.; Loscos‐Arenas, Jordi; Mermoud, Andre; Lozano, Esther; D'Alessandro, Elisa; Rebolleda, Gema; Rodriguez‐Agirretxe, Iñaki; Canut, Maribel; Rodriguez‐Calvo, Pedro P.; ,
Abstract: Purpose: To compare the supraciliary versus intrascleral implantation of the hema implant (Esnoper V‐2000) in terms of the efficacy and safety in nonpenetrating deep sclerectomy (NPDS). Patients and methods: Prospective, randomized, unmasked, competitive and multicenter clinical trial. Eighty‐three eyes from 83 patients suffering from open‐angle glaucoma (40 males, 43 females) were enrolled and followed up for 12 months. Main outcome measures were best‐corrected visual acuity (BCVA), intraocular pressure (IOP), perimetry (mean defect, MD and Visual Field Index, VFI), pachymetry, number of antiglaucoma medications and analysis of blebs according Moorfields Bleb Grading. Results: The IOP was significantly reduced in both groups from 23.74 ± 6.9 mmHg (implant sutured to the sclera, group 1) and 23.46 ± 6.47 mmHg (implant placed in the suprachoroidal space, group 2) to 15.43 ± 4.27 mmHg (p < 0.001) and 14.62 ± 3.64 mmHg (p < 0.001), respectively. There were no statistically significant differences in mean IOP values between the groups a year after the surgery (p = 0.581). BCVA did not show statistical differences in comparison with baseline (p = 0.09, group 1; p = 0.42, group 2). The mean number of antiglaucoma medications was reduced in both groups from 2.58 ± 0.04 and 2.68 ± 0.02 before the surgery to 0.32 ± 0.76 and 0.24 ± 0.66 after surgery. Conclusion: Nonpenetrating deep sclerectomy using hema implant (Esnoper V‐2000) is safe and effective regardless of the positioning of the implant. We achieved IOP decrease and reduction in antiglaucoma medications during the first year after surgery without significant differences between both techniques.